Optical and mass spectra from reactive plasma at magnetron deposition of tantalum oxynitride - Dudin, S.; Yakovin, S.; Zykov, A.; Yefymenko, N. (Вопросы атомной науки и техники, 2021)
Processes in reactive plasma during the magnetron deposition of tantalum oxynitride with ICP activation of reactive gas are studied in dependence on Oxygen fraction. Results of spectroscopic study of optical emission from the plasma and of mass-spectrometry of gas composition in the vacuum chamber in response to ignition of magnetron discharge and inductively coupled plasma are presented. It is shown that dissociation level of all species grows with the magnetron current increase while its dependence on oxygen/nitrogen ratio is non-monotonic.